ANALISIS PENERAPAN GOOD MANUFACTURING PRACTICE (GMP) DI CV. SUMBER TIRTA JAYA BANYUWANGI - Nita Kuswardhani; Yuli Wibowo; R. Dio Alif Pratama (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Water is one of the basic needs that is very important for human life. One of the most important things needed by humans is drinking water. Now many companies are producing bottled drinking water to meet the needs of the community. Along with these developments, the issue of quality assurance and product safety, especially bottled drinking water products, continues to grow according to consumers' demands and requirements and the level of life and human well-being. One way to attract consumer confidence in product safety is to ensure that the drinking water products produced are safe for health and that the treatment process complies with the government's standards. The purpose of this study is to Analyze the application of Good Manufacturing Practice, Assess the application of Good Manufacturing Practice, and Recommend improvements related to the application of Good Manufacturing Practice in CV. Sumber Tirta Jaya Banyuwangi. Analysis of the application of GMP was carried out by referring to the regulation of the Minister of Industry of the Republic of Indonesia No. 75 of 2010 regarding how to process food processing properly with a questionnaire accompanied by a fishbone method to identify the factors of GMP irregularities and brainstorming methods in order to recommend improvements from the deviation in the application of GMP that occurred. Based on the study results, from 178 sub-aspects of GMP response examination taken from the regulations of the Ministry of Industry of the Republic of Indonesia, 31 total deviations are consisting of 18 minor deviations, four significant deviations and nine critical deviations. Critical deviations include the aspects of buildings, employees, facilities sanitation, and process control of machinery and product contamination.